2010
DOI: 10.1590/s1677-55382010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Total prostatectomy within 6 weeks of a prostate biopsy: is it safe?

Abstract: Purpose: Many urologists recommend a six-week time interval between a prostate biopsy and a total prostatectomy (TP) to allow the biopsy induced inflammation to subside. Our aim was to assess whether the time interval between prostate biopsy and TP has an impact on the surgical outcome. Materials and Methods: A retrospective analysis was performed on data from patients who underwent a TP by a single surgeon from 1992 to 2008. The patients were divided into two groups according to the time interval between biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…We recorded demographic and clinicopathologic variables and compared these variables between subgroups of biopsy-to-surgery interval <4 weeks and ≥4 weeks for each group. To assess the immediate operative outcome, we set the primary endpoint as positive surgical margin status and the secondary endpoints as operative time and estimated blood loss, as in most of the previous studies ( 4 , 5 , 6 , 7 , 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded demographic and clinicopathologic variables and compared these variables between subgroups of biopsy-to-surgery interval <4 weeks and ≥4 weeks for each group. To assess the immediate operative outcome, we set the primary endpoint as positive surgical margin status and the secondary endpoints as operative time and estimated blood loss, as in most of the previous studies ( 4 , 5 , 6 , 7 , 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, urologists tend to recommend an interval of at least 4 weeks after prostate biopsy before radical prostatectomy to allow biopsy-induced inflammation or hematoma to subside ( 3 ). However, studies have shown that early radical prostatectomy does not affect immediate operative outcomes such as operative time, estimated blood loss, and positive surgical margin status for either conventional radical retropubic prostatectomy ( 4 , 5 , 6 ) or robot-assisted laparoscopic radical prostatectomy ( 7 , 8 , 9 ). Nonetheless, to our knowledge there are no studies evaluating this subject with respect to the surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most studies supported the opinion that the interval between the biopsy and surgery was not related to the perioperative outcomes even in open prostatectomy. [ 21 23 ] Furthermore, undergoing the prostatectomy as soon as possible may be beneficial for patients in high risk group (higher PSA level or Gleason scores). [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…A fair number of studies have been carried out on surgical outcomes compared according to the interval from prostate biopsy to surgery. 7 8 9 Lee et al . 5 showed, on a series of 169 patients, no significant correlation in perioperative outcomes and complications with the interval after biopsy.…”
mentioning
confidence: 99%